POTENSI DAN PEMANFAATAN ONGGOK DALAM RANSUM UNGGAS - Kiramang, Khaerani (Teknosains: Media Informasi Sains dan Teknologi, 2011)
Cassava waste is well known as one’s of agroindustry waste. Cassava waste can caused pollution because its high water. It’s make microorganism can grow well in the waste and produce odor to environt. That’s cause a serious pollution problem if we don’t care to the waste. Cassava waste potential to be a feedstuff but its low nutrition need some treatment to enhance the nutrition. Cassava Waste high in fiber and low protein. Several research have done to know how far cassava waste can used as a feedstuff. As the research, applied biotechnology to the cassava waste enhance crude protein about 1000% , reduce crude fiber and HCN. The other hand, cassava waste fermented increase amino acids and vitamins. Poultry Feeding cassava waste fermented can support performance and productifity of broiler and laying hens. Kata kunci:Cassava waste, rations, poultry.